Punishment : the supposed justifications. - Honderich, Ted ("Middlesex, Eng", 1984)
The book is given over to the analysis and assessment of arguments. It is its somewhat grand intention to consider every- thing that is intelligible and at all persuasive by way of defenses of the practice of punishment, and also to pay some attention to persistent obscurities. These defenses and obscurities are principally the work of a succession of moral philosophers.
Keywords: Punishment